Controlled lateral packing of insulin monolayers influences neuron polarization in solid-supported cultures - Grasso, Ernesto Javier (2013)
Neurons are highly polarized cells, composed of one axon and several branching dendrites. One important issue in neurobiology is to understand the molecular factors that determine the neuron to develop polarized structures. A particularly early event, in neurons still lacking a discernible axon, is the segregation of IGF-1 (Insulin like Growth Factor-1) receptors in one neurite. This receptor can be activated by insulin in bulk, but, it is not known if changes of insulin organization as a monomolecular film may affect neuron polarization. To this end, in this work we developed solid-supported Langmuir–Blodgett films of insulin with different surface packing density. Hyppocampal pyramidal neurons, in early stage of differentiation, were cultured onto those substrates and polarization was studied after 24 h by confocal microscopy. Also we used surface reflection interference contrast microscopy and confocal microscopy to study attachment patterns and morphology of growth cones. We observed that insulin films packed at 14 mN/m induced polarization in a similar manner to high insulin concentration in bulk, but insulin packed at 44 mN/m did not induce polarization. Our results provide novel evidence that the neuron polarization through IGF-1 receptor activation can be selectively modulated by the lateral packing of insulin organized as a monomolecular surface for cell growth.